AFFIRMATIVE ACTIONS AT THE STATE UNIVERSITY OF MATO GROSSO DO SUL: AN ANALYSIS OF EFFECTS ON THE BLACK STUDENTS' IDENTITIES - Renato Oliveira Santana; José Licínio Backes (Editora da Universidade de Santa Cruz do Sul, 2013)
This paper aims at analyzing the effects of higher education on the black students' identities at the State University of Mato Grosso do Sul. This study has been inspired by authors who understand identities as processes that are in continuous negotiations, articulations and tensions. Black students admitted to the State University of Mato Grosso do Sul in 2004 who were favored by the quota policy were interviewed. The black subjects have developed a complex identity negotiation that has shown to be in a constant dialogue, which is under tension with the colonial discourse. The permanence in higher education represents the occupation of an important time/space for the affirmation of these subjects' identities.